2019
DOI: 10.1002/pon.5223
|View full text |Cite
|
Sign up to set email alerts
|

Greater mindfulness associated with lower pain, fatigue, and psychological distress in women with metastatic breast cancer

Abstract: Objective Women with metastatic breast cancer (MBC) report high levels of disease‐related symptoms including pain, fatigue, psychological distress, and sleep disturbance. Mindfulness may be particularly relevant to women with MBC given the high symptom burden and psychological toll of this disease; however, the topic is understudied among this patient population. Therefore, we aimed to test the associations between mindfulness and patient‐reported symptoms among a sample of women with MBC. Methods Sixty‐four w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 36 publications
(163 reference statements)
2
40
0
Order By: Relevance
“…Nonjudgment and nonreactivity to inner experience emerge as particularly strong facets of mindfulness that associate with psycho-behavioral symptoms in cancer patients (Zimmaro et al, 2020), and our findings further emphasize the importance of these two facets of mindfulness in women with breast cancer. Yet, our findings are distinct in that we report associations between within-person changes in these two facets of mindfulness in response to an MBSR intervention and improvement in psycho-behavioral symptoms and quality of life.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Nonjudgment and nonreactivity to inner experience emerge as particularly strong facets of mindfulness that associate with psycho-behavioral symptoms in cancer patients (Zimmaro et al, 2020), and our findings further emphasize the importance of these two facets of mindfulness in women with breast cancer. Yet, our findings are distinct in that we report associations between within-person changes in these two facets of mindfulness in response to an MBSR intervention and improvement in psycho-behavioral symptoms and quality of life.…”
Section: Discussionsupporting
confidence: 68%
“…For example, in a community sample, higher levels of the nonjudgment facet of mindfulness predicted lower levels of depression, anxiety, and stress-related symptoms (Cash & Whittingham, 2010). In individuals with cancer, distinct facets of dispositional mindfulness have also been found to relate to positive psychological outcomes and reduced symptom distress (Poulin et al, 2016; Zimmaro et al, 2020). An evaluation of breast and gastrointestinal cancer patients with neuropathic pain, revealed greater dispositional mindfulness to be associated with lower self-reported pain and depression, and better mental health-related quality of life, with nonjudgment and acting with awareness the most consistent facets related to better mental health outcomes (Poulin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 59 Furthermore, mindfulness-based interventions also positively affect other symptoms, such as fatigue, distress, and pain in patients with cancer. 60 , 61 Therefore, we suggest that mindfulness-based interventions should be considered an effective treatment option for reducing short-term and medium-term anxiety among adults with cancer. Comparing mindfulness-based interventions with other effective interventions for anxiety, such as drugs and behavioral therapies, should be the focus of future research in adults with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies have reported that the impact of advanced breast cancer patients enduring cancer-related-fatigue (CRF) is extensive (Hsieh et al, 2019;Kinkead et al, 2018;Zimmaro et al, 2019)). Most cancer patients reside with CRF because of their cancer treatment and diagnosis.…”
Section: Introductionmentioning
confidence: 99%